Nonlinear transport and fluctuation characteristics of doped semiconductors - Katilius, R.; Liberis, J.; Matulionis, A.; Raguotis, R.; Sakalas, P. (Nonlinear Analysis: Modelling and Control, 1998)
Fluctuation phenomena in doped n-type GaAs, at moderate applied electric fields being influenced by interelectron scattering, are interpreted in terms of effective electron temperature. Electron Fick’s diffusion coefficients in longitudinal and transfer direction are estimated.